«DOMINICA MATTINA CHE SI FANNO GLI INCANTI...» ΑΦΕΤΗΡΙΑ ΓΙΑ MIA ΕΡΕΥΝΑ - ΜΠΑΡΟΥΤΣΟΣ ΦΩΤΗΣ (Eoa kai Esperia, 1997)
The public auctions (incanti) hald in Venetian Crete during the late 16thcentury have not up till now attracted the interest of researchers, although theyconstituted a widely accepted institution.The first attempt to reveal the context —function and application— of theincanti was designated by two basic deductions: a)not only public priperty wasout up for auction and b) it was not only real estate sold by it, but movableproperty as well, namely income from real estate.These deductions, supported by the evidence the documents of the incantiprovided, led to another one. This type of rublic auction was the main mechanismthrough which financial friction between individuals was resolved. The differencebetween a creditor and a debtor would be settled by the introduction of thelatter’s assets —movable or not— to auction, as long as the procedural prerequisiteshad been fulfilled to the last.